STING inhibition in myocardial remodelling following myocardial infarction. (14th October 2021) - Rech, L; Abdellatif, M; Poettler, M; Stangl, V; Ulcar, E; Ablasser, A; Rainer, P P
Abstract: Background: Myocardial infarction (MI) is one of the prevalent causes of death in the world, with some patients developing heart failure from myocardial remodelling after infarction. Inflammatory processes trigger remodelling post-MI. One inflammatory factor is Type 1 Interferon which can be released by cytosolic dsDNA, sensed via the STING-receptor. The aim of this study was to reduce this inflammatory response by inhibiting the STING-receptor and thus reduce post-infarctional remodelling. Methods: Surgery was performed to trigger infarction for 30 minutes by ligating of the proximal LAD in 22 wildtype male mice (C57BL6/J), another 10 mice have undergone sham operation. Echocardiographic assessment of the endocardial systolic fractional area change (FAC) was carried out before, one day after and three weeks after surgery. The mice with ligation were separated into two groups with eleven individuals each, as well as the sham operated mice in five each group. One group was treated with the STING-Inhibitor while the other received a control substance. Treatment was applied intraperitoneally once per day for three weeks. Results: – Procedural success was good as evidenced by immediate FAC decline in MI animals. – One day post-op no significant difference in FAC and infarct size can be seen between the two groups of MI mice – Three weeks post-op a highly significant difference in FAC can be observed in the group treated with STING-Inhibitor compared to the control group in the MI mice – The sham operated mice never showed any difference between the groups at any time. – Fibrosis and Cross sectinal area significantly reduced in treated MI group compared to control – Ifi44 and Cxcl10 expression levels in the infarct area showed significant reduction in the inhibitor MI group compared to the control MI group after three weeks Conclusion: STING-Inhibitor potentially improves outcome after a myocardial infarction. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Research Area Network on Cardiovasczlar Diseases (ERA-CVD) PhD-Program Molecular Medicine - Medical Unviersity of Graz